Chronic Airflow Obstruction in a Black African Population: Results of BOLD Study, Ile-Ife, Nigeria. (2nd January 2016) - Obaseki, Daniel O.; Erhabor, Gregory E.; Gnatiuc, Louisa; Adewole, Olufemi O.; Buist, Sonia A.; Burney, Peter G.
Abstract: Global estimates suggest that Chronic Obstructive Pulmonary Disease (COPD) is emerging as a leading cause of death in developing countries but there are few spirometry-based general population data on its prevalence and risk factors in sub-Saharan Africa. We used the Burden of Obstructive Lung Disease (BOLD) protocol to select a representative sample of adults aged 40 years and above in Ile-Ife, Nigeria. All the participants underwent spirometry and provided information on smoking history, biomass and occupational exposures as well as diagnosed respiratory diseases and symptoms. Chronic Airflow Obstruction (CAO) was defined as the ratio of post-bronchodilator (BD) one second Forced Expiratory Volume (FEV1 ) to Forced Vital Capacity (FVC) below the lower limit of normal (LLN) of the population distribution for FEV1 /FVC. The overall prevalence of obstruction (post-BD FEV1 /FVC < LLN) was 7.7% (2.7% above LLN) using Global Lung Function Initiative (GLI) equations. It was associated with few respiratory symptoms; 0.3% reported a previous doctor-diagnosed chronic bronchitis, emphysema or COPD. Independent predictors included a lack of education (OR 2·5, 95% CI: 1.0, 6.4) and a diagnosis of either TB (OR 23.4, 95% CI: 2.0, 278.6) or asthma (OR 35.4, 95%CI: 4.9, 255.8). There was no association with the use of firewood or coal for cooking or heating. The vast majority of this population (89%) are never smokers. We conclude that the prevalence of CAO is low in Ile-Ife, Nigeria and unrelated to biomass exposure. The key independent predictors are poor education, and previous diagnosis of tuberculosis or asthma.